A unified class of compound lifetime distributions. Issue 8 (17th April 2016) - Rodrigues, Josemar; Cordeiro, Gauss M.; de Castro, Mário; Nadarajah, Saralees
Abstract: A flexible class of lifetime distributions is obtained by compounding the first activation and the last activation survival functions proposed by Rodrigues et al.(2011), which possess nice biological and physical interpretations. In this compound scheme, the number of competing causes of the event of interest has a general discrete distribution characterized by its probability generating function. We demonstrate that several models recently introduced in the literature can be derived as special cases of the proposed model.